ASPEK SUSTAINABILITY SUPPLY CHAIN TERHADAP KEPUTUSAN PEMBELIAN MOBIL LCGC PREFERENSI CUSTOMER JAKARTA - Paduloh Paduloh; Humiras Hardi Purba; Vardian Giovanni; Deny Wibisono (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
This study was made to know the features of any vehicle feature on which decisions of consumers inJakarta when it took the decision to choose a vehicle. The method of research by giving questionnairesto 120 respondents and data processed using SPSS 16 to determine the degree of importance, usingdescriptive analysis and frequency. This study was conducted based on the number of vehiclemanufacturers of four-wheel vehicles in LCGC (Low Cost Green Car), researchers wanted to knowwhether the feature LCGC effect on supply chain sustainability. Feature - a feature built into thequestionnaire is physical endurance and durability of the product, engine performance and Type latestmachinery, Recycling of plastic materials and metals, the use of environmentally friendly raw materials,the ethical aspects and environmental supplier, the price of the vehicle, the number of passengers in thevehicle and the shape and models of vehicles. based on the results of the questionnaire which featuresare most influential in determining the selection of a vehicle is the price of the vehicle, followed bynumber of passengers, and then features eco-friendly materials and performance and the latest enginetypes. Based on the degree of interest of 95% consider price feature becomes an important factor even40% thought it very important. For features an environmental friendly raw materials use 100% of therespondents agreed to consider these important features.